Analisis Tindakan Sosial Tradisi Nadran Masyarakat Desa Muara Gading Mas Kabupaten Lampung Timur - Gilas Anti Ampera; Mulia, Cut Aja; Ruslin; Jamal, Muh. (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
Abstract The nadran tradition or sea alms is a tradition that developed in several coastal areas in Indonesia, one of which is in Muara Gading Mas Village, East Lampung Regency. For most of the wider community, especially religious communities, ritual actions that are not based on the teachings of a particular religion are considered incorrect. However, rituals that often appear in the life of certain communities also often cannot be separated from the use of religious symbols such as prayers. This tradition is interpreted as a manifestation of gratitude for the abundant marine products and hope for safety when going to sea. This research is qualitative research with a sociological approach that tries to explore the relationship between religion and the people of Muara Gading Mas Village towards the Nadran tradition. Furthermore, the social motives for this traditional celebration will be analyzed. The results of this research are that people understand this tradition in various ways. Among the people's understandings are as a spiritual force to bring safety and prosperity to them, as a reinforcement of social values among them, and as a form of preserving the original culture of their ancestors. Meanwhile, the motives for social action against this tradition are also varied, such as the motive for traditional social action, value rationality action, and instrumental social action. Keywords: Nadran; Marine Alms; Social Action. Abstrak Tradisi nadran atau sedekah laut adalah tradisi yang berkembang di beberapa daerah Pesisir di Indonesia, salah satunya ada di Desa Muara Gading Mas, Kabupaten Lampung Timur. Bagi kebanyakan masyarakat luas, terutama masyarakat beragama, tindakan ritual yang tidak dilandaskan pada ajaran agama tertentu dianggap tindakan yang tidak benar. Namun, ritual yang sering nampak dalam kehidupan komunitas tertentu juga seringkali tidak dapat dilepaskan dari penggunaan simbol-simbol agama seperti doa-doa. Tradisi ini dimaknai sebagai perwujudan rasa syukur atas hasil laut yang melimpah dan pengharapan keselamatan dalam melaut. Penelitian ini adalah penelitian kualitatif dengan pendekatan sosiologis yang mencoba menggali relasi antara agama dan masyarakat Desa Muara Gading Mas terhadap tradisi nadran. Lebih jauh, motif sosial terhadap perayaan tradisi ini akan dianalisis. Hasil dari penelitian ini adalah masyarakat memahami tradisi ini bermacam-macam. Di antara pemahman masyarakat tersebut adalah sebagai kekuatan spiritual untuk membawa keselamatan dan kesejahteraan pada mereka, sebagai penguat nilai sosial di antara mereka, dan sebagai bentuk pelestarian budaya asli leluhur mereka. Sedangkan, motif tindakan sosial terhadap tradisi ini juga beragam, seperti motif tindakan sosial tradisional, tindakan rasionalitas nilai, dan tindakan sosial instrumental. Kata Kunci: Nadran; Sedekah Laut; Tindakan Sosial.